Impact of endogenous compounds and oxidation on microbial transglutaminase-induced gelation of muscle protein from different fish / Sochaya Chanarat - Sochaya Chanarat (Prince of Songkla University., 2016)
Thesis (Ph.D., (Food Science and Technology))--Prince of Songkla University, 2015